Impact of fungicide application volume on ASIAN rust control and soybean crop yield - de Souza, Diego Miranda (2022)
Multisite fungicides are an anti-resistance strategy to control Phakopsora pachyrhizi. Among the protective fungicides, mancozeb is a fungicide that has been highlighted. However, the interaction between the fungicide spray solution and application volume is very complex. Therefore, the goal of this work is to evaluate the effect of the application volume and the combination of fungicides with different modes of action on Asian soybean rust (ASR) control and crop yield. The fungicides mancozeb, and a mix of trifloxystrobin plus prothioconazole, and a combination of mancozeb and the mix were applied over two crop seasons, 2016/2017 and 2017/2018. Every week, the disease severity caused by the fungus P. pachyrhizi was evaluated. Fungicide spraying started with the occurrence of the first pustules of disease. Subsequently, the data were used to calculate the area under the disease progress curve (AUDPC). All fungicide treatments reduced the AUDPC. The trifloxystrobin plus prothioconazole fungicide mixture was impacted to a greater extent by a reduction in application volume. The fungicide mixture with trifloxystrobin plus prothioconazole and mancozeb resulted in a lower AUDPC. It is possible to control ASR disease only with mancozeb. The effect of the application volume and the spray solution have an impact on disease control under particular crop season conditions. The lower application that provides the maximum control of SAR and greater productivity is dependent on the disease severity.